2005
DOI: 10.1037/1076-898x.11.4.256
|View full text |Cite
|
Sign up to set email alerts
|

When Static Media Promote Active Learning: Annotated Illustrations Versus Narrated Animations in Multimedia Instruction.

Abstract: In 4 experiments, students received a lesson consisting of computer-based animation and narration or a lesson consisting of paper-based static diagrams and text. The lessons used the same words and graphics in the paper-based and computer-based versions to explain the process of lightning formation (Experiment 1), how a toilet tank works (Experiment 2), how ocean waves work (Experiment 3), and how a car's braking system works (Experiment 4). On subsequent retention and transfer tests, the paper group performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
256
3
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(286 citation statements)
references
References 30 publications
17
256
3
4
Order By: Relevance
“…This assertion can be supported by Hays' (1996) and Rieber, Tzeng, and Tribble's (2004) findings on the superiority of animation over static visuals. The above results, however, challenge Mayer et al's (2005) idea that only static illustrations effectively reduce extraneous cognitive load. The addition of animation appeared to have acted as an engaging tool, assisting the EFL participants to attend to the crucial information in the multimedia texts.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This assertion can be supported by Hays' (1996) and Rieber, Tzeng, and Tribble's (2004) findings on the superiority of animation over static visuals. The above results, however, challenge Mayer et al's (2005) idea that only static illustrations effectively reduce extraneous cognitive load. The addition of animation appeared to have acted as an engaging tool, assisting the EFL participants to attend to the crucial information in the multimedia texts.…”
Section: Discussionmentioning
confidence: 69%
“…Some researchers (Mayer, Hegarty, Mayer & Campbell 2005, Schnotz, Bockheler & Grzondziel 1999, Tversky, Morrison & Betrancourt 2002 demonstrated that animation was an ineffective strategy, compared to other types, in learning. For instance, Schnotz, Bockheler, and Grzondziel (1999) conducted a research examining learning from texts and pictures together with an analysis of possible effects of animation and interactivity on knowledge acquisition.…”
Section: Visualisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alesandrini (2002) explains that from an instructional viewpoint, graphics can facilitate learning: a) when used to represent actual people, places, or things; b) when the graphic helps to simplify difficult, complex, and/or abstract material (e.g., a company's organizational chart) ; or c) when used as an analogical bridge between familiar, already learned materials and unfamiliar, or to be learned materials (e.g., a graphic of a familiar truck to facilitate learning the functions of an unfamiliar red blood cell). Repeatedly, studies have shown that graphics can benefit comprehension, insight, and learning when properly selected and used within instructional materials (e.g., the review by Tversky, Morrison & Betrancourt, 2002) Mayer and his colleagues (e.g., Mayer, 2001;2008, Mayer, Hegarty, Mayer & Campbell, 2005Mayer & Moreno, 2002;2003;Mayer & Sims, 1994) have repeatedly examined the impact of graphics on learning as they developed their cognitive theory of multimedia learning. A key assumption within that theory is that as humans encounter new information, separate verbal and visual information processing systems are used.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, research had revealed that dynamic images are not permanently effective compared to the series of static images when depicting the same contents. A research by Mayer, Hegarty, Mayer and Campbell [14], found that static images in the instructional material were more effective compared to dynamic images. In their research, two MIM methods were used to depict the concept of storms and lightning formation.…”
Section: Static Image or Dynamic Image?mentioning
confidence: 99%